POTENTIAL ANALYSIS OF PROPOLIS COMPOUND INHIBITION ON PROTEIN RECEPTOR IN BREAST CANCER USING MOLECULAR DOCKING AND MOLECULAR DYNAMICS SIMULATION METHODS - Vivianna Simanjuntak, Masrina
Breast cancer is the second most common cancer in the world and is the leading cause of cancer death in women caused by genetic damage to cells. The disease causes cells to divide and grow abnormally, forming malignant tumors, and attacking the surrounding breast tissue down to the nearest lymph nodes or to other organs in the body. Therefore, it is important to detect it early to prevent the spread of cancer and determine effective treatment. Some receptors have been linked to breast cancer control and chemotherapy is also carried out through suppression of receptor activity such as the estrogen receptor alpha (ER?), Heat Shock Protein 90 (HSP90), and NUDIX hydrolase type 5 (NUDT5). These three proteins play a role in breast cancer activity including breast tumor growth, invasion, and breast cancer metastasi. Suppression of the activity of such protein receptors is carried out by hormonal therapy or by inhibitor compounds. However, hormonal therapy and the use of inhibitor compounds still show adverse side effects to patients. On the other hand, propolis is an herbal compound that is rich in benefits due to its biological activity. The content of propolis compounds varies depending on the type of plant that is the source of food for bees and the species of bees. In general, propolis compounds consist of polyphenol compounds, namely flavonoids, phenolic acids, and esters, which are suspected to have anti-tumor properties. Today, the in silico approach with bioinformatics is important in drug candidate discovery because it has been shown to speed up the drug discovery process by reducing the time required, resources, and enabling molecular estimation before the synthesis process is carried out. In this final project, the bionformatics method including molecular docking and molecular dynamics simulations are used to see the potential of propolis compounds in inhibiting protein receptor activity in breast cancer. Estimation of ADMET parameters was also carried out to predict the physicochemical properties and toxicity of propolis compounds. The results obtained include 124 propolis compounds obtained from Nano Center Indonesia data, 115 of which meet the Lipinski rule and 86 have low toxicity properties. There are 6 propolis compounds that cannot be estimated for toxicity due to the limitations of the dataset from the software used. The prediction of hepatotoxicity properties shows that 122 propolis compounds do not have the potential to give rise to